2022
DOI: 10.3390/agronomy12040854
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Yield Parameters, Dry Matter Distribution, Nutrients Uptake, and Distribution in Strawberry (Fragaria × ananassa Duch.) cv. ‘Elsanta’ as Influenced by Spent Mushroom Substrates and Planting Seasons

Abstract: The performance of autumn and spring-planted strawberry cv. ‘Elsanta’ in peat and peat supplemented with fresh spent mushroom substrate (SMS) of Agaricus bisporus, Lentinus edodes, and Pleurotus ostreatus in 15% and 25% was evaluated. The morphological and yield parameters, dry matter distribution, uptake, and partitioning of macro- and micronutrients were studied. The experiment was carried out during 2020–2021 in an unheated tunnel and was laid out in a randomised complete block design in five replicates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…In our study different minerals were analyzed i.e., potassium, iron, zinc, calcium, cupper and manganese. The published literature suggest that mineral levels of strawberry cultivars are influenced by factors i.e., environmental conditions, growth temperature, genetics, cultivation soil as well as harvesting time (Prasad et al, 2022). Our findings regarding minerals levels for are significantly differing among tested varieties.…”
Section: Discussionmentioning
confidence: 53%
“…In our study different minerals were analyzed i.e., potassium, iron, zinc, calcium, cupper and manganese. The published literature suggest that mineral levels of strawberry cultivars are influenced by factors i.e., environmental conditions, growth temperature, genetics, cultivation soil as well as harvesting time (Prasad et al, 2022). Our findings regarding minerals levels for are significantly differing among tested varieties.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, Cu was positively associated with Zn. Prasad et al [ 46 ] also reported the synergy of Cu and N in strawberries, thus confirming the importance of Cu in N uptake and vice versa.…”
Section: Resultsmentioning
confidence: 80%
“…N, P, K, and S are essential in plant life processes such as respiration and photosynthesis, osmotic regulation, energy transfer, protein synthesis, enzyme activation, and many others [ 12 ]. According to Prasad et al [ 46 ] and Tohidloo et al [ 47 ], the positive significant correlation among N, P, and K is necessary for better strawberry development which determines the balance between vegetative growth, fruit quality, and reproductive processes. Therefore, positive interactions between Zn and these nutrients indicate the contributing role of a higher macronutrient supply in the development of the plant, including the root system, which also promotes the absorption of micronutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Due to growing environmental concerns, the proper disposal and handling of excess SMS accumulation are essential. Current research has clearly indicated that, due to its high fertilizing value, agricultural application is the most efficient method for SMS recycling [7][8][9][10]. SMS is a valuable source of organic matter and nutrients that is readily available to plants [8,11,12].…”
Section: Introductionmentioning
confidence: 99%